Microcontext of the Educational Change: Adoption and Resistance - Šidlauskienė, Virginija (Acta Paedagogica Vilnensia, 2006)
The article presents the diffusion of educational innovations at the secondary school. A common problem for many teachers, organizations and educational policy makers is how to speed up rate of diffusion of an innovation. According to the research results teachers demonstrate innovativeness to which they adopt new ideas than others school community members. Author revealed five adopter categories on the basis of their innovativeness: innovators, early adopters, early majority, late majority and laggards which correlate to teachers’ socioeconomic characteristics, personality variables, communication behaviour and prior conditions: previous practice, felt needs and problems, innovativeness and norms of educational organization. The data analysis showed the reaction of the teachers to change including acceptance, indifference (apathy, loss of interest in work, doing the minimum to get by), passive resistance – doing as little as possible. The sources of resistance are identified and ways of addressing resistances to educational change has indicated.